Teamwork and communication in oncological care: integrative review (Research, Society and Development, 2022)
Objective: to identify the challenges of teamwork and communication in hospital cancer care. The Rayyan platform hosted the 1721 productions identified. Method: the PRISMA methodology (PAGE et al., 2021) was used in the analysis of titles and abstracts, by two independent evaluators, in double blind. 39 productions were read in full. Nine met the criteria and were included. A synoptic table organized the summaries of the analyses. Results: communication challenges among professionals; reporting the severity and terminality of cases; psychological distress associated with leadership; moral distress in professionals; professional intervention based on honesty, empathy and effective communication; team climate in the therapeutic process. Conclusion: it is concluded that the oncological complexity demands an articulated and integrated action of professional teams, collective goals and effective communication.